Symulacja całkowita zgody małżeńskiej (kan. 1101 § 2 KPK) w wyroku Roty Rzymskiej c. Erlebach z 22.10.2015 r. - Góralski, Wojciech (Ius Matrimoniale, 2016)
The author presents and provides a comment on the final sentence handed down in the third instance (the Roman Rota) in a nullitatis matrimonii case, examined ob simulationem totalem at the complainant’s request (a negative and a positive sentences were handed down in the first and second instance respectively). The key issue in this case was determining whether in the examined case the complainant’s personal goals (fines operantis), namely the desire to improve the economic situation of her and her child, can be combined with the institutional goals of marriage (fines operis). By referring to judicature of the Roman Rota and thoroughly examining the case files, the adjudication panel c. Erlebach ruled that the complainant’s personal goals were consistent with the goals of the institution of marriage and that the woman has not ruled out ipsum matrimonium. Therefore, total simulation of marriage did not happen at the time the marriage was concluded.